2011
DOI: 10.1121/1.3628326
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying seismic survey reverberation off the Alaskan North Slope

Abstract: Shallow-water airgun survey activities off the North Slope of Alaska generate impulsive sounds that are the focus of much regulatory attention. Reverberation from repetitive airgun shots, however, can also increase background noise levels, which can decrease the detection range of nearby passive acoustic monitoring (PAM) systems. Typical acoustic metrics for impulsive signals provide no quantitative information about reverberation or its relative effect on the ambient acoustic environment. Here, two conservati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 13 publications
0
36
0
Order By: Relevance
“…First, a set of PSD spectra was computed over the 0.2-24 kHz frequency range using a 1024 point FFT size with 50% overlap, then all PSD spectra over a 0.5 s interval were averaged. This relatively short time interval was chosen to increase the odds that a sperm whale click would not be incorporated into the average because the click interval of a single sperm whale is generally greater than 0.5 s. The ambient noise level was then calculated by taking the minimum value of the summed pressure spectral density over the 2-10 kHz frequency band every 4 s (Guerra et al, 2011). By taking the minimum, PSD samples contaminated by sperm whale click spectra could be rejected.…”
Section: Limits Of Detection and Tracking Range As A Function Of Smentioning
confidence: 99%
“…First, a set of PSD spectra was computed over the 0.2-24 kHz frequency range using a 1024 point FFT size with 50% overlap, then all PSD spectra over a 0.5 s interval were averaged. This relatively short time interval was chosen to increase the odds that a sperm whale click would not be incorporated into the average because the click interval of a single sperm whale is generally greater than 0.5 s. The ambient noise level was then calculated by taking the minimum value of the summed pressure spectral density over the 2-10 kHz frequency band every 4 s (Guerra et al, 2011). By taking the minimum, PSD samples contaminated by sperm whale click spectra could be rejected.…”
Section: Limits Of Detection and Tracking Range As A Function Of Smentioning
confidence: 99%
“…Greene & Richardson 1988, Dragoset 1990, 2000, Caldwell & Dragoset 2000. In many instances, we found that the time be tween seismic pulses was occupied by a series of multiple arrivals of the same reverberated pulse immediately following the original (Guerra et al 2011(Guerra et al , 2016, thus inundating the soundscape with near-continuous elevated noise levels. Our study also illustrates that seismic airgun noise in the northern Gulf of Mexico propagated over a large spatial scale of several hundred kilometers, exposing a wide range of species and habitats to chronically elevated noise levels.…”
Section: Discussionmentioning
confidence: 94%
“…The resultant application of an acute sound exposure metric does not account for the chronic noise characteristics of reverberated and reflected seismic impulses after propagation over many 10s of kilometers or more (Guerra et al 2011(Guerra et al , 2016. Moreover, none of the currently implemented mitigation measures protect nonmammalian marine organisms, despite the evidence that supports the conclusion that noise exposure can both subtly and drastically affect their physiology or behavior (National Research Council 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, vessel operations near an oil production island in the Beaufort Sea raised background levels by more than 20 dB over ambient levels (Blackwell and Greene, 2006). Similarly, reverberation from airgun pulses during seismic exploration increased background noise by 30-45 dB within 1 km of the seismic ship (Guerra et al, 2011).…”
Section: Introductionmentioning
confidence: 99%